Analysis of Blood Cholinesterase Enzyme Levels Among Farmers - Sunuh, Herlina Susanto; Politon, Fellysca V. M.; Christine, Christine; Novarianti, Novarianti; Doda, Diana Vanda D. (MEDICA (International Medical Scientific Journal), 2026)
Pesticides are chemical substances used to control or eradicate pests and are considered toxic compounds that may pose health risks to farmers. Organophosphate pesticides can enter the human body through the digestive system, respiratory tract via inhalation, and unprotected skin surfaces. This study aimed to analyze the association between educational level, knowledge, spraying position, spraying frequency, length of employment, and blood cholinesterase levels among farmers in Parigi Moutong Regency. This study employed an analytical observational design with a cross-sectional approach. A total of 41 pesticide-spraying farmers from Balinggi Jati Village were included as respondents using a purposive sampling technique. Data collection was conducted through interviews using structured questionnaires and blood cholinesterase examinations performed by health personnel from Prodia Laboratory, Palu. Data were analyzed using the Chi-square test. The results showed that there were no statistically significant relationships between age and blood cholinesterase levels (p = 0.846), educational level (p = 0.879), gender (p = 0.548), length of employment (p = 0.854), spraying frequency (p = 0.252), spraying position (p = 0.132), and knowledge level (p = 0.879). In conclusion, age, gender, educational level, knowledge, spraying position, spraying frequency, and length of employment were not significantly associated with blood cholinesterase levels among farmers in Parigi Moutong Regency. Nevertheless, continuous education regarding safe pesticide use and the implementation of proper occupational safety practices remain important to minimize the risk of pesticide exposure among farmers.